The IP Multimedia Subsystem (IMS): Session Control and Other Network Operations - Russell Travis (American : McGraw -Hill, 2007)
Seamlessly merge the Internet with cellular and wireless networks using next-generation IMS technology and the comprehensive information contained in this authoritative resource. The IP Multimedia Subsystem: Session Control and Other Network Operations details the steps necessary to deliver Web-based content, VoIP, streaming multimedia, conference calls, and text messages across one integrated network. Learn how to transition to IMS architecture, communicate with legacy networks, control sessions using SIP, and connect subscribers to network services. In-depth coverage of the latest IMS security, business intelligence, customer care, and billing procedures is also included.
*
Migrate legacy networks to IMS-based technology
*
Use the Proxy, Interrogating, and Serving Call Session Control Functions
*
Interface with TDM-based, wireless, wireline, and VoIP networks
*
Handle private and public user identities, domain names, and URLs
*
Establish SIP sessions and connect subscribers to network services
* Deploy reliable network, access, and user-level security
* Prevent eavesdropping, DoS, message tampering, and amplification exploits
*
Track services rendered and charge subscribers using DIAMETER and CDRs
Keywords: Multimedia subsystem